SETBP1 Mutations Drive Leukemic Transformation in ASXL1-Mutated MDS - Inoue, Daichi (Leukemia, 2014)
Mutations in ASXL1 are frequent in patients with myelodysplastic syndrome (MDS) and associated with adverse survival yet the molecular pathogenesis of ASXL1 mutations are not fully understood. Recently it has been found that deletion of Asxl1 or expression of C-terminal-truncating ASXL1 mutations (ASXL1-MT) inhibit myeloid differentiation and induce MDS-like disease in mice. Here, we find that SETBP1 mutations (SETBP1-MT) are enriched among patients with ASXL1-mutated MDS patients and associated with increased incidence of leukemic transformation as well as shorter survival, suggesting SETBP1-MT play a critical role in leukemic transformation of MDS. We identify that SETBP1-MT inhibit ubiquitination and subsequent degradation of SETBP1, resulting in increased expression. Expression of SETBP1-MT, in turn, inhibited Pp2a activity, leading to Akt activation and enhanced expression of posterior Hoxa genes in ASXL1 mutant cells. Biologically, SETBP1-MT augmented ASXL1-MT-induced differentiation block, inhibited apoptosis, and enhanced myeloid colony output. SETBP1-MT collaborated with ASXL1-MT in inducing AML in vivo. The combination of ASXL1-MT and SETBP1-MT activated a stem cell signature and repressed the TGF-β signaling pathway, in contrast to the ASXL1-MT-induced MDS model. These data reveal that SETBP1-MT are critical drivers of ASXL1-mutated MDS and identify several deregulated pathways as potential therapeutic targets in high-risk MDS.